Pengelolaan Kesuburan Lahan Kering Masam Mendukung Ketahanan Pangan Nasional - Niluh Putu Sri Ratmini; Yeni Eliza Maryana (Seminar Nasional Lahan Suboptimal, 2021)
Ratmini NPS, Maryana YE.  2021. Management of dryland fertility support national food security. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 80-88.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The development of dryland as agricultural land is one option that has the potential to increase crop production to meet national food needs. Obstacles encountered in the management include: low soil fertility, low organic matter, deficiency of P, K, Ca and Mg, high solubility of Al, Fe and Mn, high soil acidity which have potentially toxic plants. Potential as agricultural land is quite extensive and is capable of producing if it is managed using effective technology and crop management approaches and integrated land resources. Dryland productivity is still low and the cropping index is mostly still once a year.  The purpose of this paper is to provide an overview of the potential of dry land and its development opportunities for agricultural.  Efforts should be made to increase the fertility of acid dry land are through the application of appropriate technology.